PRINSIP KETERBUKAAN SEBAGAI PERLINDUNGAN INVESTOR DALAM TRANSAKSI LUAR BURSA (OVER THE COUNTER) SEBAGAI TRANSAKSI DALAM PASAR MODAL INDONESIA - Meisy Kartika Putri Sianturi; Bismar Nasution; Suhaidi Suhaidi; Mahmul Siregar (USU LAW JOURNAL, 2014)
ABSTRACT   Bapepam Rule Number: III.A.10 on securities transactions issued in 1997, among other terms governing the transaction outside the stock exchange, the inter-company transactions between the company's securities or securities with other parties that are not regulated by the stock exchange, and transactions between persons who are not corporate securities. This study aims at finding out 1). How arrangements and transactions practice OTC (over the counter) in the Indonesian capital market 2). How does the principle of openness as an investor in a transaction protection OTC (over the counter) in the Indonesian capital market 3). What forms of fraud that occurred in the transaction counter (over the counter) and the urgency of forming regulations that accommodate OTC transactions investor protection. It was found out that 1). Bapepam Regulation No.III. No.A. 10 of the Securities Transaction no offensive presence OTC transactions (over the counter) but not a complete set of the transactions OTC (over the counter). 2). This could lead to legal uncertainty in practice-counter transactions (over the counter) and less protection for investors who transact OTC (over the counter). Unlike the practice of OTC transactions in foreign countries such as the United States, Hong Kong and Singapore where the transaction OTC (over the counter) specifically stipulated in a separate regulation. The absence of special arrangements for OTC transactions (over the counter) in the Indonesian capital market led to the lack of transparency as a principle of regulation in particular the protection of investors in the transaction OTC (over the counter). 3). Instances of corruption that occurred in transactions outside the stock exchange is the inaccurate information that issuers of securities companies more concerned with function brokerage fee without losing the security aspect, which is often distorted information data and value securities issuers. Keywords: Transactions, Over the Counter, Disclosure Principles, Investor Protection, Indonesian Capital Market